Fibrin clot structure in patients with congenital dysfibrinogenaemia. (January 2016) - Casini, A.; Duval, C.; Pan, X.; Tintillier, V.; Biron-Andreani, C.; Ariëns, R.A.S.
Abstract: The clinical phenotype of patients with congenital dysfibrinogenaemia is highly heterogeneous, from absence of symptoms to mild bleeding, or thrombosis. A few mutations are associated with a specific phenotype, but generally the clinical course is not predictable. We investigated whether fibrin clot properties are correlated with the patient's phenotype and/or genotype. Ex vivo plasma fibrin clot characteristics, including turbidity, fibrinolysis, clot permeability and fibrin fibre density assessed by laser scanner confocal microscopy were investigated in 24 genotyped patients with congenital dysfibrinogenaemia compared to normal pool plasma. Compared to normal pool plasma, the patients were characterised by slower fibrin polymerisation (lag time, 345.10 ± 22.98 vs. 166.00 s), thinner fibrin fibres (maximum absorbance, 0.15 ± 0.01 vs. 0.31), prolonged clot lysis time (23.72 ± 0.97 vs. 20.32 min) and larger clot pore size (21.5 × 10 − 9 ± 4.48 × 10 − 9 vs. 7.96 × 10 − 9 cm 2 ). Laser scanning confocal microscopy images confirmed disorganised fibrin networks in all patients. Patients with tendency to bleed showed an increased permeability compared to asymptomatic patients ( p = 0.01) and to patients with a thrombotic history ( p = 0.02) while patients with thrombotic history had a tendency to have a prolonged clot lysis time. Fibrin clot properties were similar among hotspot mutations. Further studies including a larger number of patients are needed to evaluate whether analysis of permeability and clot lysis time may help to distinguish the clinical phenotype in these patients and to assess differences according to the genotype. Highlights: Dysfibrinogenemic patients with tendency to bleed showed an increased permeability compared to asymptomatic and thrombotic dysfibrinogenemic patients. Dysfibrinogenemic patients with thrombotic history had a tendency to have a prolonged clot lysis time. Evaluation of permeability and clot lysis time may help to distinguish phenotypes in patients with dysfibrinogenemia.